First document on the presence of Iraqi Dirofilaria immitis - atia, Amall hassen; Y. Yakoob‎, Aleia (The Iraqi Journal of Veterinary Medicine, 2009)
Canine dirofilariasis in Iraq was thought not present. This is the first report of dogheartworms in our country. Hearts of 22 dogs from various sites in Kerbala province wereexamined for Dirofilaria immitis infection. Peripheral blood from dogs with worms in theheart was examined for microfilaria. Adult worms were found in 16 (73%) hearts.Microfilaria in blood not tackled in the present work. From these finding we hypothesis thatheartworm disease is usually present in / or imported from those areas that are endemic forcanine dirofilariasis